Tensile fracture strength of cracked composite laminates - Govindan Potti P.K.; Nageswara Rao B.; Srivastava V.K. (My University, 2025)
A modification in the Whitney-Nuismer stress fracture criteria known as point stress criterion and average stress criterion was proposed to improve the accuracy while evaluating the notched tensile strength of composite laminates. The adequacy of the proposed procedure is examined by considering the existing fracture data on various cracked configurations of composite laminates.